Molecular-genetic characterization of Avian avulavirus 20 strains isolated from wild birds - K. O. Karamendin; M. Kh. Sayatov; A. I. Kydyrmanov; E. T. Kasymbekov; S. E. Asanova; K. D. Daulbayeva; E. Ya. Khan (Вопросы вирусологии, 2019)
Introduction. Previously unknown paramyxovirus strains were isolated from wild birds in 2013-2014 in Kazakhstan and subsequently identified as representatives of the novel Avian avulavirus 20 species. The aims and tasks were molecular genetic characterization of novel avulaviruses and investigation of their phylogenetic relationships. Material and methods. Embryonated chicken eggs were inoculated with cloacal and tracheal swabs from wild birds with subsequent virus isolation. The complete nucleotide sequences of viral genomes were obtained by massive parallel sequencing with subsequent bioinformatics processing. Results. By initial infection of chicken embryos with samples from 179 wild birds belonging to the Anatidae, Laridae, Scolopacidae and Charadriidae families, 19 hemagglutinating agents were isolated, and five of them were identified as representatives of new viral species. The study of their sequenced genomes revealed their similarity in size, but there was a significant genetic variability within the species. 2,640 nucleotide substitutions were identified and 273 of them were non-synonymous, influencing the protein structure of viruses. It was shown that isolates Avian avulavirus 20/black-headed gull/ Balkhash/5844/2013 and Avian avulavirus 20 /great black-headed gull/Atyrau/5541/2013 were 86% and 95% respectively identical to the previously described reference strain, indicating a significant evolutionary divergence within species. Discussion. The authors suggest the existence of two independent lineages - the Caspian, represented by the reference strain Aktau/5976 and Atyrau/5541, as well as the second, geographically significantly distant Balkhash lineage. Conclusion. The study confirms the role of the birds of the Laridae family as the main reservoir of Avian avulavirus 20 in the avifauna that plays a key role in maintaining viruses of the genus Avulavirus in the biosphere and is a potential natural source for the emergence of new viral variants. Continuous surveillance of them in the wild is one of the most important tasks in ensuring the safety of the poultry industry.